From Planned Economy to the Internet Era: Economic Behavior Transformations of Russian Customers - N. V. Barinova; V. R. Barinov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
One of the most significant lines in economic studies is investigation of economic behavior of individual. The article analyzes key approaches to studying economic behavior of agents within the frames of behavioral economics that arouses higher and higher interest today. The authors provide definitions of the term ‘economic behavior’ that can be found in academic literature. The principle content of the article is made up by studying economic behavior of Russian customers in conditions of economic transformations within the period from the 1970-s to the early 21st century. The research marked stages of economic reforms of this period and analyzed the impact of different factors on shaping the model of behavior in each of the mentioned periods. The authors draw conclusions about trends of developing economic behavior of customers in the era of digitalization and introduction of artificial intellect in the field of making economic decisions.